Tissue expression of SKA1 (Spindle kinetochore-associated complex 1) in oral cancers and oral potentially malignant disorders: An association with disease progression - Khan, Samreen; Muhammad Mohiuddin Alamgir; Uzma Bukhari; Muhammad Shuja Farrukh; Quratulain (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the tissue expression of spindle kinetochore-associated complex sub-unit 1 in both oral squamous cell carcinomas and oral potentially malignant disorders, and to evaluate its association with the two lesions. Method: The analytical, cross-sectional study was conducted at Dow University of Health Sciences, Karachi, and comprised clinically and histopathological confirmed biopsy samples of oral squamous cell carcinoma and oral dysplasia that were collected from the Otolaryngology ward/outpatient department of Dr Ruth Pfau Civil Hospital Karachi, Dr Ishrat-ul-Ebad Khan Institute of Oral Health Sciences, Karachi, and the histopathology section of Dow Diagnostic Reference and Research Laboratory, Karachi, during July 2022 and April 2023. Detailed clinical history as well as radiological and histopathological findings were noted. Tissue expression of spindle kinetochore-associated complex sub-unit 1 was analysed on the samples through immunohistochemistry. Data was analysed using SPSS 21. Results: Of the 90 cases, 45(50%) had oral squamous cell carcinoma; 34(75.6%) males, 11(24.4%) females, 24(53.3%) aged <50 years and 21(46.7%) aged >50 years. The remaining 45(50%) cases had oral potentially malignant disorders; 35(77.8%) males, 10(22.2%) females, 24(53.3%) aged <50 years and 21(46.7%) aged >50 years. Tissue expressions of spindle kinetochore-associated complex sub-unit 1 were strongly positive in 25(55.6%) cases of oral squamous cell carcinoma and 13(28.9%) cases of oral potentially malignant disorders. Moderately positive expressions were seen in 20(44.4%) cases of oral squamous cell carcinoma and 32(71.1%) cases of oral potentially malignant disorders (p<0.05). In oral squamous cell carcinoma cases, strong tissue positivity was observed in poorly differentiated tumours compared to moderately differentiated and well-differentiated tumours (p<0.05). In cases of oral potentially malignant disorders, strong positivity was seen in grade III dysplasia compared to grades I and II (p<0.05). Conclusion: There was a significant difference between tissue expressions of spindle kinetochore-associated complex sub-unit 1 in oral squamous cell carcinoma and oral potentially malignant disorders, and this difference was more pronounced in different tumour grades of oral squamous cell carcinoma and in varying grades of dysplasia in oral potentially malignant disorders. Key Words: Oral squamous cell carcinoma, Oral potentially malignant disorders, Immunohistochemistry.